Developing a survey tool to measure human factors constructs for Personal Hearing Protector (PHP) use among industrial workers—first phase - Fauzan, Nur Syafiqah; Widia, Mirta; Sukadarin, Ezrin Hani (2023)
The survey tool (questionnaire) is one of the most widely used tools to collect data. This paper aims to develop a survey tool of human factors and personal hearing protector (PHP) use among industrial workers. The survey tool is developed based on the combination of the Health Promotion Model (HPM) and Health Belief Model (HBM). Development of the eight main constructs in the survey included narrative literature and qualitative review by the two expert panels of researchers in the related field. Overall, this tool produced good comments from the experts. Some of the items were removed due to poor match in terms of content. This current research is crucial to investigate the factors and PHP usage among targeted industrial workers. This study can serve as the primary instrument for determining the human factors and personal hearing protectors used for industrial workers in various sectors. This survey tool can contribute to an improved understanding of the human factors that may influence the consistent use of PHP in an excessive noise work area